The spread of infectious diseases by the transportation of stock; and their prevention - Champlin, Floyd A. (My University, 1902)
Introduction: Nature of animal diseases. Health and disease. An animal is a complex machine endowed with certain attributes; its existence is dependent upon the performance of various functions, allotted to particular organs which are composed of suitable materials. When these organs are intact and capable of performing their respective duties; when the functions upon which the life of the individual depends are in perfect and harmonious action; and when the laws which regulate them and adapt them to the influences of the external world are in full force—then we say the animal is in a state of good health. But when this organism is submitted to certain influences or conditions which hinder or prevent a part or all of its component functions, a number of phenomena are manifested to which the term disease is applied.
Citation: Champlin, Floyd A. The spread of infectious diseases by the transportation of stock; and their prevention. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Animal Diseases; Infectious Diseases; Animal Husbandry; Stock; Theses; Manuscripts (documents)